PERSEPSI DAN SIKAP WANITA TANI TERHADAP AGROINDUSTRI PANGAN DI KABUPATEN BANTUL - Supriyati, - (9-772301-994005, 2012)
The women role in farm activity of agroindustry development is very close with their perception and correlating with motivation of them to create attitude such as cognitive, affective, and conative.  Aims of this research were to observe the perception, motivation, and attitude of the women who work in food agroindustry in Bantul Regency.  The method of this research was descriptive analytical by applying survey. Sample of area was taken with different level including 4 subdistricts  and  4 villages as the main centre of food agroindustry  and that was taken 60 households using random, while the analysis method were used in this research were scoring and table analysis. The results showed  that perception of women farmers to process of food agroindustry is positive especially  on increasing of  family income  by 61 %, so  that result gave them motivation to increase income, basic need, safety by 80,84 %. The conclusion of this results was attitude of the women farmers based on cognitive, affective, and conative categories as high more than 90%, this means a good performasnce . It is suggested that government should support them with stimulants and training for improving farmers welfare.